Early cluster formation during rapid cooling of an Al–Cu–Mg alloy: In situ small-angle X-ray scattering. (November 2015) - Schloth, P.; Menzel, A.; Fife, J.L.; Wagner, J.N.; Van Swygenhoven, H.; Drezet, J.-M.
Abstract: The formation of Cu–Mg clusters in an Al–Cu–Mg aluminum alloy is observed by small-angle X-ray scattering during cooling. Cooling rates are choosen to mimic the different conditions obtained at the surface and in the center of large forgings. Clusters of 0.45 nm start to form at 250 °C. Their volume fraction depends strongly on the cooling rate and the amount of excess vacancies. The difference in cluster kinetics explains the difference in rapid hardening across large forgings.